2021
DOI: 10.3390/nano11123405
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nanoparticles on Fire Retardancy of Pedunculate Oak Wood

Abstract: Traditional flame retardants often contain halogens and produce toxic gases when burned. Hence, in this study, low-cost, environmentally friendly compounds that act as fire retardants are investigated. These materials often contain nanoparticles, from which TiO2 and SiO2 are the most promising. In this work, pedunculate oak wood specimens were modified with sodium silicate (Na2SiO3, i.e., water glass) and TiO2, SiO2, and ZnO nanoparticles using the vacuum-pressure technique. Changes in the samples and fire cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…There are several groups of nano FRs, including clay-based, carbon-based, silica-based, metal oxides, layered double hydroxides, and others, such as bio-sourced nano FRs [23][24][25]; among these, the latter have not been studied in detail as additives to UPRs, but have been successfully incorporated to other thermosetting resins, such as epoxy [26,27]. Nano FRs are also widely applicable for other polymers [28], as well as for wood [29][30][31], standing as a sustainable construction material.…”
Section: Nanoparticles As Flame Retardants For Uprmentioning
confidence: 99%
“…There are several groups of nano FRs, including clay-based, carbon-based, silica-based, metal oxides, layered double hydroxides, and others, such as bio-sourced nano FRs [23][24][25]; among these, the latter have not been studied in detail as additives to UPRs, but have been successfully incorporated to other thermosetting resins, such as epoxy [26,27]. Nano FRs are also widely applicable for other polymers [28], as well as for wood [29][30][31], standing as a sustainable construction material.…”
Section: Nanoparticles As Flame Retardants For Uprmentioning
confidence: 99%
“…Nanocomposite fire retardants induce the formation of char and prevent char oxidation. It forms a thermal insulation layer on the wood and prevents the release of volatiles for further combustion [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The bending strength, elasticity modulus, compressive strength, surface hardness, tensile strength, and shear strength of the composite modified wood were improved up to 83.9%, 82.3%, 72.7%, 48.3%, 38.4%, and 53.1%, respectively [12]. Kačíková et al demonstrated that wood modifications using sodium silicate and nanoparticle systems have potentially enhanced flame retardant properties [13].…”
Section: Introductionmentioning
confidence: 99%